The Effect of the Implementation of Project-Based Learning Model on Improving Literacy and Numeracy of Grade V Elementary School Students - Asnaria Asnaria; Umar Abdullah; Juhana Juhana (Yayasan Sembilan Pemuda Indonesia, 2026)
The average literacy and numeracy scores of Indonesian students are still below the minimum standard, with PISA 2018 achievement in the level 1 category and only 30% of students achieving basic competencies in the National Assessment. This study aims to analyze the effect of the PjBL model on improving the literacy and numeracy skills of fifth-grade students at SD Negeri 1 Banyuasin III. PjBL was chosen because it is considered relevant to the cognitive development stage of students aged 10–11 years and supports the integration of real contexts in learning. This study used a quantitative method with a nonequivalent pretest-posttest control group quasi-experimental design. The sample consisted of 56 fifth-grade students divided into experimental and control groups. The instruments used included empirically validated literacy and numeracy questions and an analytical rubric based on cognitive and contextual indicators. Data analysis was performed using MANOVA. The results showed that the PjBL model had a significant effect on improving literacy and numeracy simultaneously (Pillai’s Trace = 0.319; p = 0.000). Partially, literacy gains were higher (F = 18.195; R² = 0.252) than numeracy gains (F = 10.075; R² = 0.165), with an average N-Gain of 0.49 for literacy and 0.40 for numeracy. This effectiveness reflects the successful integration of literacy and numeracy through simple project activities. This finding implies the need to implement PjBL as a curricular strategy to support the strengthening of literacy and numeracy in the Independent Curriculum.